Aplikasi Bank Soal Ujian Kalbis Institute - Dwi Idho Handoyo (UNIVERSITAS KALBIS, 2022)
Essay bank is a process to store exam question with online method and it can also make and store exam question to the head of the major department through the application. So it's easier to make and store the exam question. The issues that appears is when the deadline is relatively short, worried that the lecture didn't covered the hard questions, and there's also the parallel class. The purpose of this research is to make a web based exam question bank to help the process of making and storing the questions. The method that this research use is system development Rapid application development (RAD) with UML model. The results of this research is a reference for the lecturer on making the exam questions and to help the process of storing the questions to the major's secretary and to the head of the major to create the making, storing, managing data structure